We slaves of Suriname - Kom, A. de (Anton), 1898-1945; McKay, David, 1973- (Cambridge, UK ; Medford, MA : Polity Press, 2022)
Anton de Kom's We Slaves of Suriname is a literary masterpiece as well as a fierce indictment of racism and colonialism. In this classic book, published here in English for the first time, the Surinamese writer and resistance leader recounts the history of his homeland, from the first settlements by Europeans in search of gold through the era of the slave trade and the period of Dutch colonial rule, when the old slave mentality persisted, long after slavery had been formally abolished. --from back cover.
Frimangron / Tessa Leuwsha -- The breath of freedom / Duco van Oostrum -- Why Anton de Kom still inspires generation after generation / Mitchell Esajas -- Foreword / Judith de Kom -- We slaves of Suriname -- "Sranan," our fatherland -- The era of slavery -- The era of "freedom" -- Reunion and farewell.
Includes index.
Keywords: Slave trade -- Suriname; Antislavery movements -- Suriname; Slaves -- Emancipation -- Suriname; Slavery -- Suriname -- History; Racism -- Suriname -- History; Esclaves -- Commerce -- Suriname; Mouvements antiesclavagistes -- Suriname; Esclaves -- Affranchissement -- Suriname; Racisme -- Suriname -- Histoire; Antislavery movements; Racism; Slave trade; Slavery; Slaves -- Emancipation; Suriname -- History; Suriname -- Histoire; Suriname; History